Contemporary tendencies in tourism - Senić, Vladimir; Manojlović, Nevena (Hotel and Tourism Management, 2017)
We live in a time of constant change, whether it be a fad, trend or megatrend. To find out today what tomorrow holds is a skill that could bring enormous competitive advantage to an individual, organization or the entire society. However, as valuable as such information about the future may be, it is just as difficult, almost impossible, to be attained with certainty. If one abandons the quest for predicting the future exactly and limits oneself to identifying probable development of a given activity, then we enter the realm of investigating the future. In this paper, the particular significance is given to longterm global trends, also known as megatrends. Such trends have a rather stable development that allows for high levels of prediction accuracy. This paper presents an overview of megatrends in tourism.